PUBLIC SPEAKING TRAINING IN EARLY CHILDHOOD - Pratiwi, Nuning Indah; Octavia, Vania Bellinda; Satria, Wahyu Indra (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Rianggede Village is a village located in Penebel, Tabanan, Bali. Rianggede Village has 4 educational units, including SDN 1.2 Rianggede, SDN 3 Rianggede, TK Kumara Santhi, and Paud Kumara Santhi. They are related to the work program that I appointed and chose Paud Kumara Santhi to implement the work program. Public speaking needs to be instilled from an early age, where public speaking helps increase the self-confidence and also creativity of the nation's children. Speaking in public is not as easy as people imagine, some children don't have self-confidence, and there are also some children who have very high self-confidence. This must be honed and prepared as early as possible, namely by training children to speak in public. In children aged 3-5 years is a phase where children have a very high sense of curiosity, therefore from the family environment and schools must instill positive things and get used to being good so that children also imitate well. The impact of upbringing greatly affects the future of the child, where if the child has a shy attitude, does not dare to ask questions during class hours, as well as other negative impacts that are harmful to the child's future, resulting in a lack of initiative and also a lack of confidence in the child.